Selection of tomato landraces with high fruit yield and nutritional quality under elevated temperatures. (29th February 2020) - Scarano, Aurelia; Olivieri, Fabrizio; Gerardi, Carmela; Liso, Marina; Chiesa, Maurizio; Chieppa, Marcello; Frusciante, Luigi; Barone, Amalia; Santino, Angelo; Rigano, Maria Manuela
Abstract: BACKGROUND: Global warming and extreme or adverse events induced by climatic fluctuations are an important threat for plants growth and agricultural production. Adaptability to environmental changes prevalently derives from a large set of genetic traits affecting physiological and agronomic parameters. Therefore, the identification of genotypes that are good yield performer at high temperatures is becoming increasingly necessary for future breeding programs. Here, we analyzed the performances of different tomato landraces grown under elevated temperatures in terms of yield and nutritional quality of the fruit. Finally, we evaluated the antioxidant and anti‐inflammatory activities of fruit extracts from the tomato landraces selected. RESULTS: The tomato landraces analyzed here in a hot climate differed in terms of yield performance, physicochemical parameters of fruit (pH, titratable acidity, degrees Brix, firmness), bioactive compounds (ascorbic acid, carotenoids, and polyphenols), and anti‐inflammatory potential. Three of these landraces (named E30, E94, and PDVIT) showed higher fruit quality and nutritional value. An estimated evaluation index allowed identification of PDVIT as the best performer in terms of yield and fruit quality under high temperatures. CONCLUSION: The analyses performed here highlight the possibility to identify new landraces that can combine good yield performances and fruit nutritional quality at high temperatures, information that is useful for future breeding programs. © 2020 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.